Rozdíly v ovlivnĕní hypoxie a anoxie CNS chlorprotixenem bĕhem ontogeneze - Staudacherová, D; Zmrhal, J; Jílek, L; Trojan, S (Sbornik lekarsky, 1975)
In the present paper the author describes the influence of the psychopharmaceutical preparation Chlorprotixen on the response of the CNS to stagnation anoxia (positive radial acceleration 10 g) and aerogenic hypoxia (15 000 m) in the course of ontogeny of the rat. Chlorprotixen increases the resistance to high altitude hypoxia, while it reduces the resistance to anoxia. The greatest differences were observed in the youngest animals.
Keywords: chlorprothixen; centrální nervový systém; Rats; hypoxie; Central Nervous System; nadmořská výška; zvířata; zrychlení; Hypoxia; Acceleration; Chlorprothixene; Altitude; krysa rodu Rattus; Animals